The relationship between the PICC tip position and weight gain, length growth of premature infants under ultrasonography: a correlation analysis study - Tao, Xiaojun; Zhang, Xianhong; Wang, Jianhui; Chen, Yanhan; Liu, Xuexiu (Frontiers in Medicine, 2023)
Objective:This study analyzed the correlation between PICC tip position and weight/length changes in preterm infants in different positions using ultrasonography. Methods:The study analyzed the distance between the PICC tip and the entrance of the heart under ultrasonography for premature infants who underwent PICC insertion. The infants were positioned and tracked weekly, and their weight and length were recorded. The Spearman rank correlation test was used to analyze the relationship between the displacement distance of the PICC tip under ultrasonography in different positions and weight/length changes. Results:A total of 202 premature infants were included in the study, and 100% of them experienced changes in the PICC tip position. During the first week, 134 (66.33%) cases in a flexed position and 153 (75.74%) cases in an straight position showed displacement of the catheter towards the heart. The displacement distance of the tip during catheter retention was significantly correlated with weight change (rs=0.681/0.661, P<0.05) and length change (rs=0.629/0.617, P<0.05).To the third and fifth week, weight increased by 451±178 and 750 (715 975) g, length increased by 1.50 (1.00 2.12) and 3.00 (2.00 3.70)cm, the catheter moved 1.27±0.89 and 2.23±0.95cm respectively in a flexed position. Conclusions:The PICC tip position in preterm infants is influenced by weight and length changes. It is crucial to use ultrasonography to track and locate the catheter within the first week of placement and to increase the frequency of catheter localization starting from the third and fifth weeks. The flexed position is recommended during catheter localization.